2010
DOI: 10.21608/jpp.2010.86594
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Rice Varieties to Phosphorous Fertilizer Under Newly Reclaimed Saline Soils

Abstract: For optimizing rice grain yield under saline conditions; the current trail has been performed during 2009 and 2010 seasons at El-Sirw Agriculture Research Station, Damietta province, Egypt. The main objective of this attempt is to find out the response of six different rice varieties namely, Sakha101, Sakha102, Sakha104, Giza177, Giza 178 and Egyptian hybrid one (Sk2034H) to various phosphorous rates i.e. 0, 30, 60 and 90 kg P2O5 ha -1 under newly reclaimed saline soil. The experiments were performed in a spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 0 publications
23
13
0
Order By: Relevance
“…The varietal differences in LAI are reflected different genetic make up. The current findings are in agreement with those reported by Alam et al (2009) and Zayed et al (2010), who revealed that hybrid rice surpassed inbred rice verities in LAI, dry matter and number of tillers.…”
Section: Rice Cultivars Performancesupporting
confidence: 94%
See 4 more Smart Citations
“…The varietal differences in LAI are reflected different genetic make up. The current findings are in agreement with those reported by Alam et al (2009) and Zayed et al (2010), who revealed that hybrid rice surpassed inbred rice verities in LAI, dry matter and number of tillers.…”
Section: Rice Cultivars Performancesupporting
confidence: 94%
“…Also, phosphorus application might be increasing phosphorus availability and subsequently increased its uptake and its content in rice plants leading to more ATP formation, that is the main stare for energy in plant and might encourage rice growth, metabolism, photosynthesis and nucleic acid resulted in high efficiency of dry matter production. The results are in agreement with those reported by Suriya-arunroj et al (2000), Kumar and Singh (2001), Biswas and Dravid (2001), Hood (2002), Ali et al (2004), Bharat (2006) and Zayed et al (2010).…”
Section: Effect Of Phosphorus Ratesupporting
confidence: 93%
See 3 more Smart Citations